The Role of Corpus Linguistics in Grammar Instruction: A Review of Literature - Alamri, Basim (International Journal of Linguistics, 2022)
The development of grammar instruction and research has begun in the past two decades (Conrad, 2000). Teaching English grammar has been delivered via a traditional method. The present study provides a literature review of how grammar instruction has been influenced by corpus linguistic (CL). The review points out the benefits of implementing corpus-based approach in grammar instruction and some difficulties encountered both teachers and students when applying CL tools. The perceptions of students and teachers towards using CL in grammar instruction was also highlighted. The results of the review showed that corpus-based approach enhanced students grammar knowledge, fostered learning autonomy, and improved students scores in grammar tasks. The review also reported some challenges, such as technical difficulties and glitches, issues in designing corpus-based materials and conducting corpus-centered activities, and increased teachers workload. Overall, the participants in the reviewed studies reported positive perceptions towards using corpus-based approach in grammar instruction. Implementing this approach helps teachers design suitable materials and students gain grammar knowledge. It is suggested that further studies are needed to investigate the effectiveness of corpus-based approach in specific grammatical aspects.